Development of temperature-responsive transmission switch film (TRTSF) using phase change material for self-adaptive radiative cooling. (15th September 2022) - Su, Weiguang; Cai, Pei; Kang, Ruigeng; Wang, Li; Kokogiannakis, Georgios; Chen, Jun; Gao, Liying; Li, Anqing; Xu, Chonghai
Highlights: The n-octadecane contents in TRTSF should be less than 30 w.t.% to avoid leakage issue. Comparing between OCT10%, OCT20% and OCT30%, the higher n-octadecane content in TRTSF the more significant switching effect. The OCT20% showed a good phase change stability and optical switching effect. The switching effect of TRTSF samples is enhanced by the thickness of the switch film. Temperature switching of TRTSF resulted by the decreased transmittance of PCM from 97% to 3.7% after solidification. Abstract: To overcome the problem of unable automatic turn on and off response to the ambient temperature of current static radiative cooling systems, we prepared a series of temperature-responsive transmission switch film (TRTSF) samples using n-octadecane as phase change material (PCM) and polydimethylsiloxane (PDMS) as carrier material. The phase change cycle permeability analysis showed that the TRTSF samples with PCM content above 30.0 w.t.% exhibit a serious leakage problem due to a large number of holes on surface. The TRTSF samples with 10.0–30.0 w.t.% PCM content were further analysed by Differential scanning calorimetry (DSC) and Thermogravimetry (TG), and compared with the theoretical PCM contents, which verified the reliability of the curing results of PCM in TRTSF from various aspects. The ultraviolet–visible light-near-infrared (UV–VIS-NIR) and mid-infrared (MIR) transmittance characterization of TRTSF revealed that the switching effect was obvious during solid–liquid phase change process. TRTSF microstructure analysis revealed that the particle size distribution of PCM microspheres was between 1 μm and 6 μm. The UV–VIS-NIR band (wavelength at 0.25–1.1 μm) transmittance of PCM decreased to less than 3.7% after solidification due to the interfacial reflectance of solid PCM particles increased to more than 66.8% even in monolayer, thus the solid PCM particles would produce Mie scattering and isolate the internal and external radiation heat transfer. However, the TRTSF can be used as the radiative cooling emission layer since its optical properties were similar to the PDMS when the PCM is in liquid phase. Overall, the TRTSF film prepared in this study successfully adapted the temperature switching properties, also, is expected to be further used for the development of self-adaptive radiative cooling systems.